Nuevas formas de administración, nuevas formas de control : la fundación de Lucus Augusti y su conventus - Dopico Caínzos, Maria Dolores (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
In this paper we will analyze a new kind of administration created by emperor Augustus in some provinces of the Empire, the conventus iuridici. It is one of the most original innovations that best expresses the depth of his reforms, although it has been little valued by some researchers. Taking as an example the conuentus Lucensis and especially its capital city, Lucus Augusti, we can understand the complexity and diversity of their functions. They were used as an original and thoughtful instrument for indigenous control, cohesion and unity and as the best example of Roman power through the iuris dictio, a concept which, as it will be seen, has been incorrectly interpreted by most researchers